Tècniques i mètodes de traducció de Francesc Alegre a La primera guerra púnica (1472). - BESCÓS, PERE (Scripta, 2017)
In 1472 Francesc Alegre translated the Italian version of the Commentarii tres de primo bello punico of Leonardo Bruni. In this article we have compared thoroughly the Catalan with six Italian manuscripts and the original text in Latin. The divergences between original and translation have been ordered in three categories: additions, eliminations and modifications. Alegre's methodology oscillates from a literal translation to a translation of original's meaning. The results of this article will be compared later with Alegre's methodology translating the Transformacions of Ovid. The ultimate objective is to define Francesc Alegre as a translator.